Impaired sleep mediates the negative effects of training load on subjective well-being in female youth athletes - Watson, A.; Brickson, S. (Sports Health: A Multidisciplinary Approach, 2018)
Background: Although increased training load (TL) and impaired sleep are associated with decreases in subjective well-being in adult athletes, these relationships among female youth athletes are unclear. It is unknown whether the effects of sleep and TL on well-being are independent or whether alterations in sleep mediate the effects of TL on subjective well-being. Hypothesis: Sleep and TL exert independent effects on subjective well-being among youth athletes, although alterations in sleep mediate a significant portion of the effect of TL on well-being in female youth athletes. Study Design: Prospective cohort study. Level of Evidence: Level 4. Methods: A total of 65 female soccer athletes (age range, 13-18 years) were monitored for 1 year. Daily TL was determined by session rating of perceived exertion and converted to z-scores. Every morning, participants recorded sleep duration in hours and rated stress, mood, fatigue, and soreness on a scale from -3 to +3 (worst to best). Linear mixed-effects models and mediation analysis were used to evaluate the independent effects of TL and sleep on well-being. Results: Average sleep duration was 7.9 ± 1.4 hours during the study period. In the multivariable model, TL and sleep duration were independently associated with fatigue (TL: ß = -0.19, P < 0.001; sleep: ß = 0.15, P < 0.001), mood (TL: ß = -0.030, P = 0.014; sleep: ß = 0.13, P < 0.001), stress (TL: ß = -0.055, P = 0.001; sleep: ß = 0.13, P < 0.001), and soreness (TL: ß = -0.31, P < 0.001; sleep: ß = 0.022, P = 0.042). Sleep duration mediated a significant portion of the effect of TL on mood (26.8%, P < 0.001), fatigue (12.6%, P < 0.001), and stress (24.5%, P < 0.001). Conclusion: Among female youth athletes, decreased sleep duration and increased TL are independently associated with impairments of subjective well-being. In addition, decreased sleep mediates a significant portion of the negative effect of increases in TL on subjective well-being. Clinical Relevance: Monitoring and promoting sleep among female adolescent athletes may significantly improve subjective well-being, particularly during periods of increased TL.